Use of QC Methods to Improve the Utilization Efficiency of Condensate Water - Xinquan Jiang; Xinqiao Jiang (Institute of Advanced Engineering and Science, 2013)
Condensation of water use for energy saving and emission reduction is of great significance, and QC methods is an effective method to improve the utilization of condensate management. This article will be the empirical study on the condensation water in the target Enterprise workshop as objects, study how to use QC method to improve the recovery rate, and to adopt effective measures to improve the production process of condensation water, eventually able to resolve their energy-saving emission reduction issues. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2368